Research on Small Grains in Support of a Short-lived Renaissance in Cereal Production in Iceland in the 1960s and Its Recent Revival - Björn Sigurbjörnsson 1931- (2014)
This report is part science and part history. It deals with research and farming activities in small grain production in Iceland half a century ago and its recent revival. It all started in 1960, increased swiftly over a few years and then disappeared, almost as swiftly, when the weather in Iceland took a turn for the worse with the arrival of – what some have called – a small ice age. It was not until the mid 1990s when grain production took wing again, coinciding with a trend towards more favourable growing conditions. In the early 1960s many farmers, a farmers´ cooperative and state and private companies started barley production on a fairly large-scale in many locations in Iceland but primarily in the south central part. Right from the beginning the Government of Iceland recognized the risk involved with grain growing in a country without grain cultivars adapted to local growing conditions. Thus, funds were made available to the Department of Agriculture of the University of Iceland Research Institute. It was given the task of testing foreign small grain cultivars and gene pools as well as to start a cereal breeding programme and associated research on fertilizer requirements and suitable cultivation techniques. This research went on for most of the 1960s until unfavourable summer weather made grain growing too risky. As all the cultivars tested during this period are now obsolete, no detailed and statistically analysed information on the performance of the different genotypes tested is presented. Research and breeding of grain, chiefly barley, did not take off again until the 1990s. Now, barley farming can be considered an established and successful agricultural industry in Iceland. Skýrsla þessi er bæði vísindi og saga. Hún fjallar um rannsóknir og ræktun á korni á Íslandi á tímabilinu milli 1960 og 1970. Niðurstöður rannsóknanna voru aldrei gerðar upp og birtar í vísindatímaritum af því að vaxandi kuldaskeið á þessum áratug kom næstum í veg fyrir þroskun korns og frekari áhuga bænda á kornrækt og ...